COCOON BIOLOGY OF EARTHWORMS OF WASTE DEPOSIT SITES OF TRIPURA (INDIA) - DEBNATH, SUSMITA; CHAUDHURI, PRIYASANKAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Earthworm species viz. Perionyx excavatus, Dichogaster bolaui, Lampito mauritii, Metaphire posthuma found in the waste deposit sites of West Tripura were reared in field soils mixed with cow dung in order to examine their growth and reproductive potential under laboratory conditions. The epigeic earthworms, P. excavatus and D. bolaui were continuous breeder with high fecundity (187 and 92 cocoons worm-1 year-1) and low incubation period (13 and 14.2 days). Anecic earthworm, L. mauritii and endogeic M. posthuma were semi-continous and discrete breeder respectively. Highest and lowest hatching success of cocoons were recorded in D. bolaui (82%) and M. posthuma (25%) respectively. Interestingly in the earthworm species, P. excavatus (1.15 hatchling-1 cocoon-1), D. bolaui (1.7 hatchling-1 cocoon-1), L. mauritii (1.8 hatchling-1 cocoon-1) more than one hatchlings emerged out from a single cocoon, whereas, M. posthuma produced only one hatchling per cocoon. Cocoon production of earthworms was significantly higher (P<.05) during summar and monsoon. Incubation periods of cocoons increased significantly (P<.05) with the rise in temperature within a temperature range of 24°C to 33°C for the cocoons produced by L. mauritii and M. posthuma while incubation periods of the cocoons shortened significantly (P<.05) with the rise in temperature in case of P. excavatus and D. bolaui. With the rise in temperature from 25°C to 32°C number of cocoon hatching increased (P<.05) in P. excavatus and D. bolaui while decreased (P<.05) in L. mauritii. In all earthworm species, biomass peaks coincide with the peak cocoon production. Continuous breeding strategies with high fecundity, hatching success and low incubation period of the cocoon in P. excavatus, and D. bolaui and semi-continuous breeding strategy of L. mauritii, indicate their possible usefulness in vermicomposting technology. The earthworm species, M. posthuma displaying discrete breeding strategy with less fecundity, long incubation period and less hatching success of the cocoon is not suitable for vermicomposting technology but can be applied along with organic matter for soil amelioration.